Progress, Challenges, and the Nexus of Research and Impact - the importance of technology in biodiversity conservation in Indonesia - Dolly Priatna; Kathryn A. Monk (Universitas Pakuan, 2023)
The Global Assessment Report on Biodiversity and Ecosystem Services 2019, published by the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES), shed light on the increasingly alarming state of global biodiversity. Biodiversity is essential to human survival through its contribution to ecosystem stability, resilience, and the provision of critical ecosystem services that sustain essential ecological processes and human well-being. Amongst other services, as demonstrated across Indonesia, biodiversity supports livelihoods by providing building and clothing materials, maintaining water quality, and providing medicines and food. As the global human population reached 8 billion in 2022, the interconnections between our unsustainable production and consumption, the climate crisis, and biodiversity decline have been increasingly recognized by the global community through IPBES and IPCC (Intergovernmental Panel on Climate Change). Escalating human numbers, coupled with burgeoning economic and industrial demands, must necessitate substantial forest land use—repositories of biodiversity. Conservation practitioners have therefore been continually driven to innovate in their pursuit of effective strategies for sustainably managing the world's precious biodiversity. Researchers and academics have the pivotal responsibility to produce research that brings about real-world impactful outcomes. The academic community is expected to address the needs of those working to conserve nature through the development of research and technology with immediate practical applicability. We look forward to publishing more of these research impact papers in the future.